2021
DOI: 10.54740/ros.2021.011
|View full text |Cite
|
Sign up to set email alerts
|

Mycological Air Quality at Animal Veterinary Practice

Abstract: The objective of the study was to characterize the mycological quality of air at animal veterinary practice in Krakow. Bioaerosol measurements were performed during the summer season of 2017. The samples of outdoor and indoor air at animal veterinary practice were collected using a 6-stage Andersen`s air sampler. The highest concentration of fungal aerosol was observed in the treatment room. The analysis showed various fungal contamination in different measuring points at different measuring times of the day. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
1
0
1
Order By: Relevance
“…The share of other isolated types of fungi, such as Aspergillus, Alternaria, Absidia, Epicoccum, Fusarium, Rhizomucor, Scopulariopsis, Trichoderma, did not exceed 31.4% of the total mycobiota of the air of the examined indoors. These results are consistent with data obtained in tests of other rooms, including residential and other commercial premises (Lee andJo 2006, Bulski andFrączek 2021). The literature on the subject shows that mold fungi, mainly of the genera Aspergillus, Cladosporium and Penicillium, may pose a particular threat to human health, as they are the most common cause of allergy to molds.…”
Section: Resultssupporting
confidence: 88%
“…The share of other isolated types of fungi, such as Aspergillus, Alternaria, Absidia, Epicoccum, Fusarium, Rhizomucor, Scopulariopsis, Trichoderma, did not exceed 31.4% of the total mycobiota of the air of the examined indoors. These results are consistent with data obtained in tests of other rooms, including residential and other commercial premises (Lee andJo 2006, Bulski andFrączek 2021). The literature on the subject shows that mold fungi, mainly of the genera Aspergillus, Cladosporium and Penicillium, may pose a particular threat to human health, as they are the most common cause of allergy to molds.…”
Section: Resultssupporting
confidence: 88%
“…As far as the problem of bacterial intoxication inside livestock facilities is concerned, it has not been studied and explained in detail yet. Available literature provides data regarding a vet clinic (Bulski et al 2019) or facilities for other livestock animals, but not horses. Matković et al (2007) studied intoxication occurrence in the stable and reported that bioaerosol concentrations indoors were 73-fold to 102-fold higher depending on the time of the day.…”
Section: Discussionmentioning
confidence: 99%
“…O Instituto Nacional de Segurança e Saúde Ocupacional da América e a Conferência Americana de Saúde Industrial Governamental (ACGIH) determinaram que o número total de partículas de bioaerossol em ambientes internos não deve exceder 1.000 UFC.m -3 , enquanto a contagem total cultivável de bactérias não deve ser superior a 500 UFC.m -3 (NIOSH, 1998;ACGIH, 1989;AIHA, 1996). Além disso, a Administração de Proteção Ambiental de Taiwan (EPA) declarou que para espaços públicos internos, a concentração de bactérias não deve ser superior a 1.500 UFC.m -3 , enquanto a concentração de fungos não deve exceder 1.000 UFC.m -3 (CHEN et al, 2016;BULSKI;FRACZEK, 2021). Entretanto, quando a razão de concentração interna/externa de fungos for menor ou igual a 1,3, o limite de concentração de fungos <1000 UFC.m -3 não se aplica (LU et al, 2018).…”
Section: Diaunclassified